INTERACTION OF AUTHORITIES WITH CIVIL SOCIETY INSTITUTIONS: SPECIFICS IN CONDITIONS OF MARTIAL LAW - Tsymbaliuk, Valerii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Aim: to outline the specifics of interaction of authorities with institutions of civil society in conditions of martial law. In this regard, the following tasks are implemented in the presented material: 1) to provide a definition of the phenomenon of civil society in connection with the research topic; 2) to reveal the typical content of interaction between authorities and institutions of civil society; 3) to show the specifics of such interaction under martial law conditions. Research methods: general theoretical and analytical methods in combination with systemic and complex approaches. Results: a set of different types of social (group) associations connected by a system of non-state relations, objectively oriented to satisfy the rights, freedoms and needs of citizens (their associations), in particular in relations with the state is determined at the theoretical level as the phenomenon of civil society. It was established that participation of civil society in the rule-making, security and social activities of the state increased significantly in the conditions of martial law. Such a situation forced the legislator to make changes to the existing legal acts regulating various spheres of public life. Discussion: the principle position for our research is the position that interaction of authorities with institutions of civil society is possible only in the legal sphere, because otherwise it contradicts the principles of the Constitution of Ukraine and current legislation in the field of public administration. At the same time, the representatives of the Ukrainian civil sector have certain problems with information and communication with the authorities, as well as the problems with the usage of public participation tools in the conditions of martial law. The indicated problem situation calls into question the effective interaction of authorities with institutions of civil society and needs its own legal solution.